[Ekslibris] Alexandra Gieysztora / Tadeusz Przypkowski. - Przypkowski, Tadeusz (1905-1977) (1941)
Tarcza herbowa z godłem rodu Gieysztorów z hełmem i klejnotem, u dołu na wstędze napis: Alexandra Gieysztora.